From stability to dynamics: understanding molecular mechanisms of regulatory T cells through Foxp3 transcriptional dynamics. (17th September 2018) - Bending, D; Ono, M
Summary: Studies on regulatory T cells (Treg ) have focused on thymic Treg as a stable lineage of immunosuppressive T cells, the differentiation of which is controlled by the transcription factor forkhead box protein 3 (Foxp3). This lineage perspective, however, may constrain hypotheses regarding the role of Foxp3 and Treg in vivo, particularly in clinical settings and immunotherapy development. In this review, we synthesize a new perspective on the role of Foxp3 as a dynamically expressed gene, and thereby revisit the molecular mechanisms for the transcriptional regulation of Foxp3 . In particular, we introduce a recent advancement in the study of Foxp3-mediated T cell regulation through the development of the Timer of cell kinetics and activity (Tocky) system, and show that the investigation of Foxp3 transcriptional dynamics can reveal temporal changes in the differentiation and function of Treg in vivo . We highlight the role of Foxp3 as a gene downstream of T cell receptor (TCR) signalling and show that temporally persistent TCR signals initiate Foxp3 transcription in self-reactive thymocytes. In addition, we feature the autoregulatory transcriptional circuit for the Foxp3 gene as a mechanism for consolidating Treg differentiation and activating their suppressive functions. Furthermore, we explore the potential mechanisms behind the dynamic regulation of epigenetic modifications and chromatin architecture for Foxp3 transcription. Lastly, we discuss the clinical relevance of temporal changes in the differentiation and activation of Treg . Graphical Abstract: